A methodology for inexpensive GPS data storage and analysis - Levin, Thomas (Proceedings from the Annual Transport Conference at Aalborg University, 2010)
The increase in the use of tenders in Norwegian transportation research is forcing the research community to think in new ways. This paper looks into using open source software and consumer grade equipment for scientific purposes. The use of consumer grade data logger and open source hardware is a viable alternative. This paper documents the methods and the tools used for three research projects, 2 are close to finishing and one has just started. Vehicle speed and positional data was collected with inexpensive data loggers and data was stored and analyzed with open source tools. The tools proved to be more powerful, but they do not offer the same graphical user interfaces. The main way to analyze data is through the use of standard SQL. Both average speed calculations using a road network ana driver behavior analysis can be carried out we few lines of code for large amounts of data.